The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/dvdy.21123
|View full text |Cite
|
Sign up to set email alerts
|

Lack of galectin‐1 results in defects in myoblast fusion and muscle regeneration

Abstract: Galectin-1 has been implicated in the development of skeletal muscle, being maximally expressed at the time of myofiber formation. Furthermore, in the presence of exogenous galectin-1, mononuclear myoblasts show increased fusion in vitro. In the current study, we have used the galectin-1 null mouse to elucidate the role of galectin-1 in skeletal muscle development and regeneration. Myoblasts derived from the galectin-1 mutant showed a reduced ability to fuse in vitro. In galectin-1 null mutants, there was evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 62 publications
4
53
0
2
Order By: Relevance
“…Recently, it has been reported that a lack of galectin-1 results in defects in myoblast fusion and muscle regeneration after cardiotoxin injury. 27 Taken together, we may suggest that galectin-1 plays an important role during tissue regeneration in response to insults in general.…”
Section: Discussionmentioning
confidence: 74%
“…Recently, it has been reported that a lack of galectin-1 results in defects in myoblast fusion and muscle regeneration after cardiotoxin injury. 27 Taken together, we may suggest that galectin-1 plays an important role during tissue regeneration in response to insults in general.…”
Section: Discussionmentioning
confidence: 74%
“…Gal1 has been suggested to play a role in skeletal muscle development [3][4][5][6]. During muscle differentiation, Gal1 is secreted and interacts with laminin in the basement membrane [4].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction has been suggested to inhibit myoblast attachment to laminin and hence fusion into myofibers [4]. However, other studies have shown a reduction in the fusion of Gal1 null myoblasts and an impaired regeneration of adult muscle fibers in Gal1 null mutant mice [5,6]. Consequently, Gal1 has been suggested to enhance skeletal muscle growth during development and adult muscle regeneration [6,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi, chez les souris dépourvues de galectine 7, on observe un retard de cicatrisation après une blessure et une prolifération anormale des kératinocytes après une exposition aux rayons UVB, indiquant que cette galectine intervient dans la répa-ration de l'épiderme [17]. De la même façon, la galectine 1 est impliquée dans la régéné-ration musculaire déclenchée par une blessure induite par l'injection de cardiotoxine [18]. Plus généralement, certaines galectines auraient un rôle dans le maintien des cellules souches musculaires et neuronales.…”
Section: Fonctions Des Galectinesunclassified